The influence of fuel properties on threshold combustion in aviation gas turbine engines - Burger, Victor (Sasol Advanced Fuels Laboratory, 2017)
This body of work investigated the influence of alternative jet fuel properties on aviation gas turbine performance at threshold combustor operating conditions. It focused on altitude blowout performance and was in part motivated by results that were encountered during an aviation industry evaluation of synthetic kerosene that complied with the Jet A-1 specification, but differed from the fuel that was used as a reference in terms of some significant properties. As a consequence the relative impact of physical properties and reaction chemistry properties were of primary interest in this study. The thesis considered the potential to blend a range of different alternative jet fuel formulations which exhibited independent variations in properties relating to evaporation and reaction behaviour whilst still conforming to legislated physical fuel specifications. It further explored the potential for said variations having a detectable and significant influence on the simulated high altitude extinction behaviour in a representative aviation gas turbine combustor. Based on the findings, appropriate metrics were suggested for scientifically quantifying the appropriate properties and conclusions were drawn about the potential impact of alternative jet fuel properties on blowout performance. These subjects were addressed primarily through the theoretical analyses of targeted experimental programmes. The experimental design adopted a novel approach of formulating eight test fuels to reflect real-world alternative fuel compositions while still enabling a targeted evaluation of the influences of both physical and chemical reaction properties. A detailed characterisation was performed of the test fuels' physical and reaction properties. The extinction and spray behaviours of the fuels were then evaluated in a laboratory scale combustor featuring dual-swirl geometry and a single prefilming airblast atomiser. The various experimental data sets were interpreted within the context of a theoretical model analysis. In doing so the relative performance of alternative jet fuel formulations under laboratory burner conditions were translated to predict relative real world altitude performance. This approach was validated against aforementioned industry evaluation results and demonstrated to be consistent. A technically defensible explanation was provided for the previously unexplored anomalous altitude extinction results that were observed during the industry evaluation of synthetic jet fuel. A conclusive case was made for the extinction limit differences having been caused by the relative differences in chemical ignition delays of the fuels. The probability of volatility (distillation profile) and fuel physical properties playing a significant role in the impaired altitude performance was discredited. Evaporation-controlled combustion efficiency was, however, shown to become a significant factor at low air mass flow rates or when the fuel evaporation is compromised. The influence of flame speed and chemical ignition delays were investigated. Laminar flame speed was shown not to correlate with LBO, discrediting its use as a proxy for reaction rate. The study showed a correlation between the lean blowout behaviour of jet fuels and the ignition delays associated with their derived cetane numbers. Additionally, there was substantive support indicating that an even stronger correlation could be obtained by operating the IQT™ device that is used to measure these delays at an elevated temperature. The thesis makes a contribution towards the development of both technical understanding and practical tools for evaluating the potential operating limits of alternative jet fuel formulations.